Time burnt away: The impact of heat-induced changes on skeletal age-at-death diagnostic features. Issue 5 (September 2022) - Rodrigues, Catarina Ochôa; Matos, Vítor M.J.; Ferreira, Maria Teresa; Gonçalves, David
Highlights: Pre- and post-burnt observations to evaluate heat impact on age-at-death scores. Heat-induced changes can affect the evaluation of morphological age-at-death features. Impact of heat-induced changes was present in both pre-calcined and calcined bones. Abstract: This paper investigates the established notion that bone calcination has a major impact on age estimation while low-intensity burns have a mere negligible impact. Few systematic researches have been carried out so far about this topic so the true impact of heat-induced changes on diagnostic age features is mostly unknown. The agreement between pre-burning and post-burning observations of age features was investigated on 51 human skeletons (22 males and 29 females with ages-at-death ranging from 61 to 93 years old) subjected to experimental burns. These skeletons belong to the 21st Century Identified Skeletal Collection housed at the Laboratory of Forensic Anthropology of the Department of Life Sciences, University of Coimbra, Portugal. The Suchey-Brooks method based on the pubic symphysis and the method developed on the auricular surface by Buckberry and Chamberlain (2002) were scrutinized. The Suchey-Brooks method provided better agreement between pre- and post-burn observations than the method from Buckberry and Chamberlain (2002). However, it became clear that heat-induced changes affected both methods regardless of heat intensity since both calcined bones and bones burnt at lower intensities often showed less than perfect agreement. Therefore, this research demonstrates that the analysis of age-at-death can be impaired in burnt bones, even those not subjected to calcination, with clear impact for forensic and archaeological investigations.